The Screening of Bacterial Insecticides against Musca domestica L. (Diptera: Muscidae) - Yamac, Mustafa (2010)
In this study, a total of 396 bacterial isolates were obtained from soil samples from Eskiş ehir, Turkey and these were screened for their antimicrobial and insecticidal activity. Only the isolates displaying weak or no activity, a total of 322, were selected for insecticidal activity studies. Two of these (39.02 and 42.04) showed insecticidal activity on Musca domestica larvae and on adult flies with topical application. The insecticidal activity of the isolates was compared to that of standard insecticidal compounds produced by actinomycetes (antimycin A, cycloheximide and nikkomycin Z) and insecticidal compounds producing collection strains (Streptomyces avermitilis NRRL 8165 and S. pactum NRRL 5230). In the primary screening program, the mortality rates of isolates 39.02 and 42.04 on M. domestica larvae were 95% and 75%, respectively. The insecticidal compounds produced by the isolates 39.02 and 42.04 were more effective by topical application than ingestion on adult flies. However, they did not show any insecticidal activity on the pupae and all pupae hatched into adult flies. The genotoxic potentials of the crude extracts from the active isolates were studied with the Umu test using Salmonella typhimurium NM2009 and NM3009 strains. The results show that all of the compounds did not have mutagenic activity. An 16S rRNA analysis of the isolates 39.02 and 42.04 shows that they belong to genera Achromobacter and Streptomyces, respectively.